The Pyroptosis-Related Long Noncoding RNA Signature Predicts Prognosis and Indicates Immunotherapeutic Efficiency in Hepatocellular Carcinoma - Wang, Tao; Yang, Yi; Sun, Ting; Qiu, Haizhou; Wang, Jian; Ding, Cheng; Lan, Ren; He, Qiang; Wang, Wentao (Frontiers in Cell and Developmental Biology, 2022)
Pyroptosis has been demonstrated in recent years to be an inflammatory form of gasdermin-regulated programmed cell death characterized by cellular lysis and the release of several pro-inflammatory factors and participates in tumorigenesis. However, the effects of pyroptosis-related lncRNAs on HCC have not yet been completely elucidated. In this study, we extracted the lncRNA expression data of HCC patients and the corresponding clinical data from The Cancer Genome Atlas (TCGA) database. According to LASSO algorithm, a novel pyroptosis-related lncRNAs prognostic risk signature model was developed based on the regression coefficients of ZFPM2-AS1, KDM4A-AS1, LUCAT1, NRAV, CRYZL2P-SEC16B, AL031985.3, SNHG4, AL049840.5, AC008549.1, MKLN1-AS, AC099850.3 and LINC01224 and then classified HCC patients into a low- or high-risk group. The high-risk score according to pyroptosis-related lncRNA was significantly associated with poor overall survival even adjusting for age, clinical stage. Receiver operating characteristic (ROC) curves and the principal component analysis further supported the accuracy of the model. Our study revealed that the higher pyroptosis-related lncRNAs risk score was significantly associated with tumor staging, pathological grade, the tumor-node-metastasis (TNM) stages. The nomogram incorporating the pyroptosis-related lncRNAs risk score and clinicopathological factors demonstrated had good accuracy. Furthermore, we observed distinct tumor microenvironment cell infiltration characteristics between high- and low-risk tumors. Notably, based on the risk model, we found that the risk score is closely related to the expression of immune checkpoint genes, immune subtypes of tumor, and the sensitivity of HCC to chemotherapy drugs and immunotherapy. In conclusion, the novel risk score of pyroptosis-related lncRNAs which we established can serve as a promising prognostic biomarker for HCC patients, At the same time, provide helps for patients to guide precision drug treatment and immunotherapy.